The power of words: the changing role of the Italian head of state during the Second Republic. Issue 4 (November 2014) - Amoretti, Francesco; Giannone, Diego
Abstract : Many authors use the metaphor of an accordion to describe the enlargement of the constitutional functions of the Italian head of state: because of the weakness of the political parties the president is able to 'open and play the accordion' according to his own interpretation of his institutional powers. While useful, this metaphor does not take into account the structural changes that have occurred over the last 30 years, as well as the informal powers that recent presidents have resorted to, which were the most important factors in the metamorphosis of the presidential figure. Structural changes include the end of the Cold War, the collapse of the First Republic and the mediatisation and personalisation of politics and party structure. Informal powers include those of ' esternazione ' (a term that roughly means 'to render public personal statements without previous consultation with the cabinet') and of moral suasion. By analysing the development of these two powers, this article aims to describe the changing role of the head of state during the Second Republic. It also defines a typology of presidential moral suasion, which is proposed as a useful tool to analyse presidential style and strategy in influencing law-making. The analysis of the innovative use of communicative powers by the last two presidents, Ciampi and Napolitano, shows how the transformation of the Italian presidency can probably be considered permanent.